Strategies to Address COVID-19 Vaccine Hesitancy and Mitigate Health Disparities in Minority Populations - Kate W. Strully; Teresa M. Harrison; Theresa A. Pardo; Jordan Carleo-Evangelist (Frontiers in Public Health, 2021)
Beyond the complex logistical task of prioritizing, distributing and safely storing millions of doses of COVID-19 vaccines, state and local governments must simultaneously devise and carry out transparent plans that center equity and overcome the barriers to vaccination facing minority communities. Using insights gleaned from four focus groups conducted with health care and social service professionals serving minority communities in New York State as well as from existing research on vaccination, our results emphasize that vaccine hesitancy and access barriers—particularly within minority communities—pose significant hurdles to achieving widespread uptake of COVID-19 vaccines. Overcoming barriers requires community-engaged campaigns that acknowledge and address the historical injustices and on-going inequities that drive distrust within communities of color, emphasize understandable and culturally appropriate messages that directly address people's concerns about vaccine safety and access, and tap existing community infrastructure to make full use of trusted voices to deliver timely and accurate information about vaccines. Given emerging data and changing conditions, campaigns must also be self-reflective and adaptive, assessing progress and outcomes and reevaluating strategies as needed. However, above all, primary goals should remain focused on transparency, equity and building trust.